Comparison of Clinical and Functional Outcomes after Platelet-Rich Plasma Injection and Corticosteroid Injection for the Treatment of de Quervain's Tenosynovitis - Kumar, Vivek; Talwar, Jatin; Rustagi, Ashish; Krishna, Loveneesh G.; Sharma, Vinod Kumar (Journal of Wrist Surgery, 2022)
Background Platelet-rich plasma (PRP) has local anti-inflammatory actions, which is being used as a treatment in various tendinopathies.Purpose The aim of the study is to compare the clinical results of PRP injection and corticosteroid injection in the management of de Quervain's tenosynovitis (DQTSV).Patients and Methods In this prospective study, 60 patients of DQTSV, fulfilling the predefined inclusion and exclusion criteria, were randomised into two groups. In group 1 (n = 30), patients received a single injection of autologous PRP and in group 2 (n = 30) they received a single injection of corticosteroid (methylprednisolone). All patients were followed up at 1 month, 3 months, 6 months, and 1 year for evaluation by Finkelstein test, visual analogue scale (VAS), DASH (Disabilities of the Arm, Shoulder and Hand) score, and Modified Mayo Wrist score (MMWS).Results In both the groups improvement occurred in Finkelstein test, VAS score, DASH score, and MMWS which were found to be statistically significant at all points of follow-ups when compared to the pre-intervention values. Comparison of scores between the two groups did not show any statistical significance. No complications were reported in PRP group. Statistically significant complications (p-value = 0.026) like subcutaneous fat atrophy, depigmentation, and temporary increase in pain were seen in eight patients in the corticosteroid group with an overall complication rate of 26.67%.Conclusion Both the modalities are equally effective in the management of DQTSV remittance. PRP is equally effective as corticosteroid in reducing symptoms of first dorsal compartment stenosing tenosynovitis. PRP may have a lower complication profile, however, this benefit should be weighed against the slight increase in cost and time of PRP preparation and injection.Level of Evidence Level 2, prospective comparative study.
Keywords: de Quervain's tenosynovitis; PRP; corticosteroid; Finkelstein test; DASH; Modified Mayo wrist score